Skeletons in the Classroom Closet: Presence/absence in the “democratic” public sphere of the academy - Provençal, Johanne (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractThe author brings together Paulo Freire and Jürgen Habermas to ask whether dialogue is possible in the classroom or whether, in a culture of rational debate, the classroom becomes more oppressive than democratic? In a voice and style that attempts to invite the skeletons out of the classroom closet, the author asks scholarly readers to lend an ear, to give audience to the tensions in the classroom and the academy. She argues that the classroom and academy are at risk of being more oppressive than democratic, and calls for what Freire describes as “witness” and trust in academic conferences, policy boardrooms, school staff rooms, and classrooms. Finally, the author extends the metaphor to scholarly publishing, and asks also about the skeletons in the closets of many scholarly journals.